2017
DOI: 10.1155/2017/1626741
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Repair with Easy-Accessible Autologous Newborn Placenta or Umbilical Cord Blood in Severe Malformations: A Primary Evaluation

Abstract: Disrupted organogenesis leads to permanent malformations that may require surgical correction. Autologous tissue grafts may be needed in severe lack of orthotopic tissue but include donor site morbidity. The placenta is commonly discarded after birth and has a therapeutic potential. The aim of this study was to determine if the amnion from placenta or plasma rich of growth factors (PRGF) with mononuclear cells (MNC) from umbilical cord blood (UCB), collected noninvasively, could be used as bio-constructs for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Karolinska Institute conducted a complex research over placental amnion capacity and mononuclear cells (MNC) with thrombocyte-rich growth factors (platelet rich growth factors -PRGF), to form stable biological materials with the support of ECM for further autologous transplant in selected cases of congenital malformations. Preliminary conclusions confirmed that the 2 types of cell cultures are promising sources of autologous tissue 31 .…”
Section: Introductionsupporting
confidence: 53%
“…Karolinska Institute conducted a complex research over placental amnion capacity and mononuclear cells (MNC) with thrombocyte-rich growth factors (platelet rich growth factors -PRGF), to form stable biological materials with the support of ECM for further autologous transplant in selected cases of congenital malformations. Preliminary conclusions confirmed that the 2 types of cell cultures are promising sources of autologous tissue 31 .…”
Section: Introductionsupporting
confidence: 53%